Reciprocal absorbing boundary condition with perfectly matched discrete layers for transient analysis of SV-P waves in a layered half-space. (15th December 2018) - Nguyen, Cuong T.; Tassoulas, John L.
Abstract: We present an extension of the combination of the Reciprocal Absorbing Boundary Condition (RABC) with Perfectly Matched Discrete Layers (PMDLs) for transient analysis of in-plane wave motion in a layered half-space. Due to the accuracy of RABC for multilayered systems, it is employed for domain truncation beyond vertical boundaries. PMDLs are particularly appropriate for handling the homogenous half-space and, herein, they are applied as excellent absorbers of waves into the half-space underlying the layered domain. Such a combination leads to solutions of problems of plane-strain wave-propagation in a layered half-space, directly in the time domain. Numerical examples are presented illustrating the accuracy, stability and effectiveness of the proposed combination. By combining two absorbing boundaries, the use of corner elements becomes unnecessary. Moreover, the long-term solution by RABCs-PMDLs is observed to be stable in the time-window of numerical examples.